Learning disabilities practice concerns and students with LD - Bakken, Jeffrey P.; Obiakor, Festus E.; Rotatori, Anthony F. (Advances in special education, 2013)
"The area of learning disabilities is constantly changing and advancing as a result of legislation, new trends, and current research investigation ... Topics addressed include inclusion, instruction in reading, mathematics, writing, and social skills, transition, assistive technology finally ending with working with families, and teacher preparation"--Page [4] of cover.